Numerical study on nonuniform heat transfer of supercritical pressure carbon dioxide during cooling in horizontal circular tube. (August 2018) - Wang, Xiaochuan; Xiang, Meijing; Huo, Hongjun; Liu, Qi
Highlights: Three dimensional conjugate heat transfer of carbon dioxide flowing in horizontal tube is simulated. Stratification in cross sections and nonuniform heat flux distributions are illustrated. The sensitivity analysis of thermophysical properties is performed. The effects of gravity and operating pressure on heat transfer are clarified. Abstract: A three-dimensional numerical investigation has been performed to study the nonuniform heat transfer of carbon dioxide (CO2 ) flows in cooled horizontal tube under supercritical pressures. It is found that the standard k - ε turbulence model with enhanced wall treatment can predict the heat transfer coefficients fairly well as compared with available experimental data. Detailed information about velocity, temperature, and thermophysical properties are captured and discussed. The results show that the heat flux on the wall-fluid coupled interface is highly nonuniform with maximal heat flux located at the top surface and minimal heat flux at the bottom surface although constant heat flux is fixed at the outer solid wall. Both the thermally induced flow acceleration and the buoyancy force contribute to the heat transfer enhancement. The effect of heat flux is further investigated and the results indicate that the decrease of heat flux leads to a narrower and sharper heat transfer coefficient profiles. Meanwhile, a larger heat flux causes much more strongly nonuniformity in the circumferential directions. It is also observed that the maximal heat transfer coefficient is decreased significantly as the operating pressure deviates away from the critical pressure. This study provides a fundamental basis for further engineering applications.